Value at risk with high frequency data - Čižmař, Adam; Tomanová, Petra; Kavřík, Dominik; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The target of this thesis is comparison of two dierent approaches for volatility modelling. Both methods use realized measures. The methods are applied on two datasets of same length, one from US markets, one from European markets. The used methods are realized GARCH model and HAR models. These methods are applied on in sample data, the model is established and then out of sample predictions are made - one day and one week ahead. On those tted and predicted values, value at risk analysis is conducted (95% and 99%) which is then backtested. The models are also compared by standard statistical tests.
Vedoucí práce: Petra Tomanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses